2010
DOI: 10.1139/y10-017
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase expression and Nrf2 signaling during hibernation in ground squirrelsThis article is one of a selection of papers published in a Special Issue on Oxidative Stress in Health and Disease.

Abstract: Mammalian hibernation is composed of long periods of deep torpor interspersed with brief periods of arousal in which the animals, fueled by high rates of oxygen-based thermogenesis in brown adipose tissue and skeletal muscle, power themselves back to euthermic (~37 degrees C) body temperatures. Strong antioxidant defences are important both for long-term cytoprotection during torpor and for coping with high rates of reactive oxygen species generated during arousal. The present study shows that the antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 33 publications
(55 reference statements)
1
13
0
Order By: Relevance
“…Biliverdin reductase (BVR) then reduces the central methene bridge of biliverdin, producing bilirubin. Similar to the results obtained in previous studies (Ni and Storey, 2010), the expression of HO-1 was augmented in hibernating animals ( Figure 1C). Also, upregulation of BVR mRNA was observed, while the levels of HO-2 mRNA levels did not get altered in pre-hibernation ( Figure 1D).…”
Section: Active Turnover Of Heme Via De Novo Synthesis and Degradatiosupporting
confidence: 91%
“…Biliverdin reductase (BVR) then reduces the central methene bridge of biliverdin, producing bilirubin. Similar to the results obtained in previous studies (Ni and Storey, 2010), the expression of HO-1 was augmented in hibernating animals ( Figure 1C). Also, upregulation of BVR mRNA was observed, while the levels of HO-2 mRNA levels did not get altered in pre-hibernation ( Figure 1D).…”
Section: Active Turnover Of Heme Via De Novo Synthesis and Degradatiosupporting
confidence: 91%
“…One may speculate that critical Ca 2+ store-related protein structures are constantly preserved in the cardiac muscles of ground squirrels, and can be operatively recruited during the transition to hibernating state. Indeed, studies have shown that in addition to regulation via G protein-coupled receptors, SOCE in cardiomyocytes is sensitive to changes in glucose homeostasis, hypoxic or ischemic events [6769], characteristic of the transition of hibernators between active and torpid states [12,22,23]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, during hibernation—arousal transitions, hibernators have to outlive a set of cardiovascular traits that would be fatal to humans and other non-hibernating mammals, e.g. violent swings in body temperature [8,17], extreme sympathetic drive during arousal [18–20], blood viscosity [21], oxidative stress [22,23], lethal ventricular fibrillation and cardiac arrhytmias [24], etc. While such deleterious conditions in cells from non-hibernating animals would normally deregulate the control of Ca 2+ -dependent processes, cardiomyocytes from mammalian hibernators exhibit a remarkable ability to adapt intracellular Ca 2+ maintenance and, thereby, contractile function [6,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…For example, introducing siRNAs that suppress the translation of the inhibitory Keap1 protein, can activate the Nrf2 antioxidant pathway . Although we have yet to explore the role of Nrf2 in the freezing wood frog, our work on a hibernating mammalian animal model that routinely decreases its core body temperature from 37 to 0 °C for days without sustaining ischemic or oxidative damage, has shown that the Nrf2 pathway is activated, and microRNAs are intricately regulated during this natural phenomenon . Studies with rodents have shown that Nrf2 knockout causes increased hepatic warm ischemia/reperfusion injury, as evidenced by increased tissue damage and altered gene expression profiles .…”
Section: Solving the Problem Of Oxidative Stress In Donor Organsmentioning
confidence: 99%